A fuzzy framework for the usability evaluation of nuclear medical equipment - Grecco, Cláudio Henrique dos Santos (Instituto de Engenharia Nuclear: Progress Report, 2015)
To avoid use errors when handling nuclear medical equipment, it is important to develop products with a high degree of usability. This can be achieved by performing usability evaluations in the product development process to detect and mitigate potential usability problems. Usability evaluation focuses on how well users can learn and use a product to achieve their goals. Thus, the usability evaluation has fast become recognized as a valuable complement to the established approaches to design good user interfaces, to reduce incidents and accidents as well the time required to learn how to use the equipment. To gather information about usability, practitioners use a variety of methods that gather feedback from users about an existing interface or plans related to a new interface. A wide range of usability evaluation methods have been proposed, but few methods focus on developing an objective and practical evaluation framework for usability. Moreover, the usability evaluations are based on human judgments and the most methods cannot fully solve the subjectivity of these evaluations. In order to remedy this deficiency, the purpose of this work is to adopt a Fuzzy Set Theory (FST) approach to establish a framework for the usability evaluation of nuclear medical equipment based on heuristics for user interface design and international standards for ergonomics of human-system interaction.